Prototipe Sistem Monitoring Pemakaian Daya Listrik Rumah Tangga Menggunakan Android - Ni'matul Ma'muriyah; Eko Hamdani (Telcomatics, 2019)
Basic electricity tariff per Kwh (KiloWatt Hour) in the city of Batam is higher than the price of electricity in other provinces in Indonesia, this is due to the management of PT. PLN Batam is carried out by a private company.Therefore the use of electric power is a special concern for customers of PT. PLN Batam, so far the customer only knows the electricity bill when it will pay so it is difficult for customers to regulate electricity usage every month.To overcome the above problems, the research team designed a prototype system that can monitor electricity usage in real-time through Android customers. The system was built using an Arduino Mega 2560 as microcontroller and a current sensor SCT-013-000. Current sensor SCT-013-000 measurement data is processed on the microcontroller then displayed on Android via HC-05 Bluetooth communication media, then the data will be stored in the SD card that has been provided. So that measurements are carried out in real-time the system uses RealTime Clock (RTC) DS3231.The results of tests that have been done show that the system or prototype is designed to be able to monitor electrical power in real-time using Android with an error rate of <3.68%.